Barriers and facilitators for self-harm prevention and surveillance: A cross-sectional study with primary health care nurses in Brazil - Amanda Sarah Vanzela; Laysa Fernanda Silva Pedrollo; Aline Conceição Silva; Isabela dos Santos Martin; Bruno Pereira da Silva; Maria Aline do Nascimento Brandão dos Santos; Jeferson Rodrigues; Márcia Astrês Fernandes; Ana Carolina Guidorizzi Zanetti; Bianca Cristina Ciccone Giacon; Guilherme Oliveira de Arruda; Kelly Graziani Giacchero Vedana (PLoS ONE, 2025)
Most individuals who die by suicide do not have contact with specialised mental health services; instead, they engage with primary health care services. This highlights the critical role of primary care in preventing self-harm and suicide. The objective of this study was to identify the barriers, facilitators, and associated factors influencing suicide and self-harm prevention and surveillance from the perspective of primary care nurses. This cross-sectional observational study used a quantitative approach and included 125 nurses from the five macro-regions of Brazil. Data concerning barriers and facilitators to self-harm prevention and surveillance, along with associated factors, were collected online using a data capture software. Instruments were based on the Theoretical Domains Framework, developed and validated for the Brazilian context. Data analysis was performed using Generalised Additive Models for Location, Scale, and Shape (GAMLSS), with distribution selection based on the Akaike Information Criterion (AIC) and the Generalised AIC (GAIC). Analyses were conducted in R (version 4.4.1) with a significance level of 5%. In terms of self-harm prevention, “knowledge and skills” was identified as a facilitator (58.1%), while “context” (75.7%) and “reinforcement” (91.7%) were recognised as barriers. For self-harm surveillance, “reinforcement” (89.8%) and “intentions” (56.5%) were identified as barriers, whereas facilitators included “knowledge and skills” (61.7%), “beliefs about consequences” (82.9%), “emotions” (55.8%), and “behavioural regulation” (61.4%). Identifying barriers and facilitators within healthcare is crucial for implementing evidence-based practices. The findings of this study can contribute to the development of more tailored self-harm prevention strategies across different regions of Brazil.